Perceptions of body image among Malaysian male and female adolescents - Khor, Geok Lin; Mohd Shariff, Zalilah; Phan, Y. Y.; Ang, M.; B., Maznah; Abdul Karim, Norimah (Singapore Medical Association, 2009)
Introduction: Body image concerns are common among adolescents as they undergo rapid physical growth and body shape changes. Having a distorted body image is a risk factor for the development of disordered eating behaviours and eating disorders. This study was undertaken to investigate body image concerns among Malaysian male and female adolescents aged 11-15 years.